The Effect of Leadership and Compensation on Employee Performance at the Central Sulawesi Provincial DPRD Secretariat - Muhammad Yusfausan Pratama (PT. Global World Scientific, 2024)
This study aims to analyze the effect of leadership and compensation on employee performance at the Secretariat of the DPRD of Central Sulawesi Province. The independent variables in this study are leadership and compensation, while the dependent variable is employee performance. The research population included all 69 employees of the DPRD Secretariat, with a sample size of 39 people determined through a simple random sampling technique using the Slovin formula with an error rate of 5%. This research uses a quantitative approach with a causal-comparative design. Data were collected through a five-point Likert scale questionnaire and tested for validity and reliability using Corrected Item-Total Correlation and Cronbach's Alpha. Data analysis was conducted through classical assumption tests, multiple linear regression analysis, and hypothesis testing using the t-test and F-test. The results of the analysis show that both leadership and compensation have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) shows that the leadership and compensation variables together are able to explain variations in employee performance with a substantial contribution. These findings indicate the importance of strengthening effective leadership and developing a fair and competitive compensation system in improving employee performance in the government sector.